Solid-state sensors based on Eu3+-containing supramolecular polymers with luminescence colour switching capability. Issue 40 (11th July 2018) - Neumann, L. N.; Calvino, C.; Simon, Y. C.; Schrettl, S.; Weder, C.
Abstract : A europium-based metallosupramolecular polymer is reported that exhibits changes of the luminescence colour in response to different types of analytes. Abstract : Polymers that exhibit changes of their luminescence colour in response to external stimuli are attractive candidates for sensing systems. We herein report the preparation of europium-based metallosupramolecular polymers, which can be processed into films and coatings that display readily detectable luminescence colour changes in response to various types of analytes.